How Problem-Based Learning Enhances Critical Thinking? An Analysis of Contexts, Methods, and Findings from Previous Research - Verawati, Ni Nyoman Sri Putu; Rokhmat, Joni; Harjono, Ahmad; Makhrus, Muh; Sukarso, AA (International Journal of Essential Competencies in Education, 2024)
This review critically evaluates the effectiveness of Problem-Based Learning (PBL) in fostering critical thinking (CT) through a systematic analysis of experimental and quasi-experimental studies from the past decade. It synthesizes evidence across diverse contexts to identify factors influencing the success of PBL, emphasizing its contextual adaptability and methodological diversity. Notably, this review not only compiles existing evidence but also provides a nuanced analysis of the contextual and methodological elements affecting PBL's success in enhancing CT. The findings reveal that while PBL is generally effective, its superiority over traditional methods is not guaranteed, with some studies reporting comparable outcomes. High-achieving students particularly benefit from PBL, although its impact on problem-solving skills—a vital component of CT—is less pronounced. These insights underline the need for tailored PBL strategies to address its limitations and optimize its benefits. This review suggests integrating complementary methods such as technology and collaborative tools to enrich PBL. Future research should explore innovative adaptations that enhance all dimensions of CT across varied educational settings, thereby maximizing the pedagogical potential of PBL. This comprehensive evaluation provides critical insights for educators and policymakers aiming to advance CT development in contemporary education.